The effectiveness of e-learning in light of the Corona pandemic from the perspective of Tikrit University students - Assist. Prof. Dr. Kahlan Ramadan Salih; Zainab Mahmoud Hamdan (Genius Journals, 2024)
The research community consists of students from Tikrit University/College of Physical Education and Sports Sciences for the academic year (2020-2021), as the size of the original community was (935) male and female students, distributed over four classes and for morning and evening studies. As for the research sample, it was chosen randomly. The number of students reached (240) male and female students, who were selected from four classes in the college. (60) male and female students were selected from each of the above classes
Keywords: Corona pandemic; Covid-19; e-learning